Recrystallization and martensitic transformation in nanometric grain size Cu-Al-Ni thin films grown by DC sputtering at room temperature - Morán; M. J. (2018)
Fil: Morán; M. J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina